The Effect of an Acceptance and Commitment Therapy-Based Self-Compassion Program on Self-Compassion and Psychological Flexibility in Mothers - Çapulacı, Rümeysa; Söner, Osman; Söner, Osman (Nature Research, 2026)
The modern parenting process has become a complex, yet needed, structure that challenges caregivers’ ability to manage their own emotional burdens and respond sensitively to their children’s developmental needs. In this context, this study aims to examine the effect of a self-compassion psychoeducation program based on Acceptance and Commitment Therapy (ACT) on mothers of non-working children aged 4–6, focusing on their levels of self-compassion and psychological flexibility. Conducted using a quasi-experimental design, the study involved 30 volunteer mothers, divided into an experimental and a control group. The experimental group received an eight-session structured psychoeducation program, while the control group received no intervention. Data collection utilized the Self-Compassion Scale and the Psychological Flexibility Scale, with measurements taken before the program, midway through the process, and at the end. Quantitative data were analyzed using MANOVA and two-factor ANOVA. The findings revealed a significant and sustained increase in self-compassion levels among participants in the experimental group, as well as positive changes in psychological flexibility scores following the intervention process. Qualitative data supported the effectiveness of the psychoeducation program, not only in enhancing emotional awareness but also in influencing attitude and behavior. Participants reported positive experiences in applying self-compassion skills to daily life and developed more accepting and sensitive approaches toward themselves and their surroundings.
Keywords: Self-compassion; Psychological flexibility; Acceptance and commitment therapy; Psychoeducation program